Manajemen Kepala Madrasah untuk Meningkatkan Budaya Kerja Guru di Madrasah Aliyah Negeri 1 Merangin Provinsi Jambi - Asnul Kabri (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to describe and analyze the principal's management in improving teachers' work culture at Madrasah Aliyah Negeri (MAN) 1 Merangin, Jambi Province. The research focuses on three main aspects: (1) how the principal manages MAN 1 Merangin, (2) how the teachers' work culture is at MAN 1 Merangin, and (3) how the principal's management improves teachers' work culture. This study employs a qualitative approach using a case study method. Data were collected through in-depth interviews, participatory observation, and documentation studies. Data analysis was conducted using the interactive model of Miles and Huberman, encompassing data reduction, data display, and conclusion drawing. Data validity was tested through source and method triangulation. The results show that: (1) The principal's management at MAN 1 Merangin includes vision-mission-based work planning, organizing human resources according to qualifications, humanistic motivation strategies, and regular but not yet optimal supervision; (2) Teachers' work culture reflects values of discipline, social integrity, morality, and work ethic that are generally good, though some weaknesses remain in discipline and openness; (3) The principal has attempted to integrate POAC management functions in developing teachers' work culture but still requires a more systematic and structured program. This study recommends strengthening the principal's transformational leadership competence and reinforcing reward and punishment mechanisms in developing teachers' work culture.